2005
DOI: 10.1128/jb.187.3.980-990.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interactions between the Carbon and Iron Utilization Regulators, Crp and Fur, in Escherichia coli

Abstract: In Escherichia coli, the ferric uptake regulator (Fur) controls expression of the iron regulon in response to iron availability while the cyclic AMP receptor protein (Crp) regulates expression of the carbon regulon in response to carbon availability. We here identify genes subject to significant changes in expression level in response to the loss of both Fur and Crp. Many iron transport genes and several carbon metabolic genes are subject to dual control, being repressed by the loss of Crp and activated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 75 publications
8
107
3
Order By: Relevance
“…5A), thus confirming the identity of the samples, the proper expression of the transgenes, and the strong Fur basal activity under our experimental conditions. 75 of the 196 selected genes have already been identified in previous transcriptome studies as Fur-and/or iron-regulated genes in E. coli (17,42), Helicobacter pylori (38,(43)(44)(45), Neisseria meningitidis (46,47), Pseudomonas aeruginosa (48,49), Campylobacter jejuni (50), Shewanella oneidensis (51,52), and Pasteurella multicoda (53). Conversely we unveiled 121 genes that have not been reported by previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…5A), thus confirming the identity of the samples, the proper expression of the transgenes, and the strong Fur basal activity under our experimental conditions. 75 of the 196 selected genes have already been identified in previous transcriptome studies as Fur-and/or iron-regulated genes in E. coli (17,42), Helicobacter pylori (38,(43)(44)(45), Neisseria meningitidis (46,47), Pseudomonas aeruginosa (48,49), Campylobacter jejuni (50), Shewanella oneidensis (51,52), and Pasteurella multicoda (53). Conversely we unveiled 121 genes that have not been reported by previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…H-NS is also required for MBR (Figure 1, A and B) apparently via its transcriptional repression of sodB (Niederhoffer et al 1990;Dubrac and Touati 2002;Zhang et al 2005), which encodes a superoxide dismutase that detoxifies ROS. Deletion of sodB completely and specifically alleviated the need for H-NS in MBR ( Figure 5F), presumably by allowing the accumulation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The following data indicate that the known H-NS role in transcriptional repression of sodB (Niederhoffer et al 1990;Dubrac and Touati 2002;Zhang et al 2005), a superoxide dismutase that detoxifies ROS, can explain H-NS function in MBR. We found that deletion of sodB, which increases superoxide levels (Liochev and Fridovich 1997), completely substituted for H-NS in MBR ( Figure 5F).…”
Section: H-ns Can Be Substituted In Mbr By Increasing Ros Levelsmentioning
confidence: 99%
“…In view of this, we must consider that other Fur-regulated genes, namely those with complex regulation involving additional factors, may not have been identified in these studies. Reports for other organisms have described a number of regulatory circuits that respond to changes in iron levels, including the stringent control pathways (72) and those involving Crp (83) or the manganese regulator MntR (38,40). These networks could potentially influence the iron-dependent Fur regulon in V. cholerae.…”
Section: Discussionmentioning
confidence: 99%